Actuando desde la distancia: GeoVisor una app de lugares seguros y no solamente una app contra la COVID-19 - Delgado Estrada, Juan Manuel (2020)
This work aims to publicize the GeoVisor Application proposal, placing us in the context of a pandemic and the common Neogeographies practiced by the Jequetepeque population. GeoVisor is intended to be an app against the COVID - 19 and for the geolocation of safe places, but acting from a distance and taking into account the ethnographic nature of the population. A collaborative project of professionals in geotechnologies facing the world scenario of the COVID-19 and within the Peruvian context, having as a study area the District of Jequetepeque in the department of La Libertad.